Synthesis, crystal structure and structure–property relations of strontium orthocarbonate, Sr2CO4. Issue 1 (9th February 2021) - Laniel, Dominique; Binck, Jannes; Winkler, Björn; Vogel, Sebastian; Fedotenko, Timofey; Chariton, Stella; Prakapenka, Vitali; Milman, Victor; Schnick, Wolfgang; Dubrovinsky, Leonid; Dubrovinskaia, Natalia
Abstract : A new orthocarbonate, Sr2 CO4, was synthesized under extreme pressure and temperature conditions of 92 GPa and 2500 K, respectively. The crystal structure of the compound s fully characterized in situ by synchrotron single‐crystal X‐ray diffraction and DFT calculations were employed to provide insight into its equation of state, Raman and IR spectra, and bonding. Abstract : Carbonates containing CO4 groups as building blocks have recently been discovered. A new orthocarbonate, Sr2 CO4 is synthesized at 92 GPa and at a temperature of 2500 K. Its crystal structure was determined by in situ synchrotron single‐crystal X‐ray diffraction, selecting a grain from a polycrystalline sample. Strontium orthocarbonate crystallizes in the orthorhombic crystal system (space group Pnma ) with CO4, SrO9 and SrO11 polyhedra as the main building blocks. It is isostructural to Ca2 CO4 . DFT calculations reproduce the experimental findings very well and have, therefore, been used to predict the equation of state, Raman and IR spectra, and to assist in the discussion of bonding in this compound.